Strengthening the Services in Early Childhood Development in the Roma Communities - Tasevska, Alma (European Journal of Social Science Education and Research, 2020)
The realistic state of the education of the Roma community illustrates the need for serious investments in resources of a human and material kind. Although the recent decade proved to be a decade of educational needs of the Roma, analyses still show the necessity for sustaining the continuity in advancing the developments of everything connected to early childhood development, as a basic sub-system in education. The research that was done had the aim of exploring the needs for strengthening the competencies and the sensibilities of work in environments with social, language and cultural specificities. The research was conducted in several stages, with focus groups as well: a questionnaire for kindergarten educators was conducted; research with a focus group of kindergarten educators was conducted; research with a focus group of parents whose children attend the kindergarten was conducted; research with a focus group of NGO representatives was conducted. The methods and techniques applied are the method of analysis, the inductive, descriptive and the method of generalization, as well as techniques of analysis of pedagogical documentation, observation,and surveying. It can be concluded that: kindergarten educators show a need towards professional development and training related to early childhood development and learning; kindergarten educators show a need towards cooperation with the community; parents showed their dissatisfaction withthe difficult adaptation of children in the kindergarten; NGO representatives stated the need for infrastructural investments, as well as investments in joint project activities between the children, educators,and parents.